(untitled) (Global Journal of Science Frontier Research, 2018)
In the present paper, the authors derived the basic analogue of extended Mittag-Leffler function by using the extended q-beta function and obtain some important results of Mittag-Leffler function in terms of generalized Wright function. Special cases are also discussed at the end section of paper.